2010
DOI: 10.1186/1471-2407-10-475
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of stereotactic body radiation therapy for primary hepatocellular carcinoma ineligible for local ablation therapy or surgical resection. Stereotactic radiotherapy for liver cancer

Abstract: BackgroundWe evaluated the long-term effect of stereotactic body radiation therapy (SBRT) for primary small hepatocellular carcinoma (HCC) ineligible for local therapy or surgery.MethodsForty-two HCC patients with tumors ≤ 100 cc and ineligible for local ablation therapy or surgical resection were treated with SBRT: 30-39 Gy with a prescription isodose range of 70-85% (median 80%) was delivered daily in three fractions. Median tumor volume was 15.4 cc (3.0-81.8) and median follow-up duration 28.7 months (8.4-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 31 publications
6
163
0
Order By: Relevance
“…Radiation therapy has currently been adopted as a definitive therapy with curative intent if the tumor is at an early stage. Particularly, stereotactic body radiation therapy can achieve high rates of locoregional tumor control as it can deliver high doses of radiation in a single treatment session or in a small number of fractions [97,98] . In locally advanced HCCs, radiation therapy can be used to relieve obstruction and improve portal blood flow if the tumor invades the biliary tree or portal vein [99,100] .…”
Section: Radiotherapies and Emerging Therapiesmentioning
confidence: 99%
“…Radiation therapy has currently been adopted as a definitive therapy with curative intent if the tumor is at an early stage. Particularly, stereotactic body radiation therapy can achieve high rates of locoregional tumor control as it can deliver high doses of radiation in a single treatment session or in a small number of fractions [97,98] . In locally advanced HCCs, radiation therapy can be used to relieve obstruction and improve portal blood flow if the tumor invades the biliary tree or portal vein [99,100] .…”
Section: Radiotherapies and Emerging Therapiesmentioning
confidence: 99%
“…[18][19][20][21][22] Other publications apply recommended EASL or mRECIST criteria. [23][24][25][26][27] A single article compared the RECIST and EASL criteria in this indication. Price et al reported in 2012 on a series of 26 patients treated for 29 CHC by SBRT by comparing the morphological evolution according to the RECIST and EASL criteria 16 ( Table 1).…”
Section: Evaluation Of Response After Sbrt For Primary Hepatic Tumorsmentioning
confidence: 99%
“…Andolino et al 13 reported that when approximately 40% of patients had a CP-B score, 37% of patients experienced >grade 3 toxicity. In Korea, Kwon et al 27 reported a 1-year OS of 93% and RILD in 2% of patients treated with either 3 × 13 Gy for tumor volumes <30 cm 3 or 3 × 10-12 Gy for tumor volumes >30 cm 3 . For larger tumors, Kang et al 16 treated 47 patients with tumors which ranged in size from 1.3 to 7.8 cm using a regimen of 3 × 14-20 Gy, with a resulting 2-year OS of 69% and grade 3 RILD of 13%.…”
Section: Current Sbrt Dosagementioning
confidence: 99%